2015
DOI: 10.1007/s10439-015-1389-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Cenderitide-Eluting Stent (CES) II

Abstract: The use of drug-eluting coronary stents has led to significant reduction in in-stent restenosis (ISR), but led to delayed endothelialization, necessitating the prolonged use of expensive anti-thrombotic drugs with their side-effects. Cenderitide (CD-NP) is a novel anti-proliferative chimeric peptide of semi-endothelial origin. Our previous work in vitro has demonstrated; that the smooth muscle cells (SMCs) were inhibited significantly more than endothelial cells (ECs) which is the desirable feature of an anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Many of the reptilian peptides possess greater stability and less adverse side effects that give them advantages over their mammalian counterparts for therapeutic use. Recently, the chimeric peptide Cenderitide, designed from the snake venom dendroaspis natriuretic peptide (DNP) [ 71 ], has been found to exert potent cardioprotective action and is being evaluated in a phase II clinical trial for the treatment of cardiac ischemia [ 23 , 24 ]. Furthermore, unlike BNP, L2 presents the advantage to have a potent antiplatelet activity [ 72 ], which makes it a drug of choice for the treatment of acute myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the reptilian peptides possess greater stability and less adverse side effects that give them advantages over their mammalian counterparts for therapeutic use. Recently, the chimeric peptide Cenderitide, designed from the snake venom dendroaspis natriuretic peptide (DNP) [ 71 ], has been found to exert potent cardioprotective action and is being evaluated in a phase II clinical trial for the treatment of cardiac ischemia [ 23 , 24 ]. Furthermore, unlike BNP, L2 presents the advantage to have a potent antiplatelet activity [ 72 ], which makes it a drug of choice for the treatment of acute myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous preclinical and clinical studies have shown that these venom-derived peptides can act on multiple disease processes that play a role in negative outcomes associated with cardiac ischemia [ 22 ]. Certain clinical results have demonstrated that venom-derived natriuretic peptides may represent a superior treatment solution by offering therapeutic benefits in chronic heart failure [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following this, a 4‐week pig study was carried out with a total of 32 stents implanted into 16 pigs . The in vivo results demonstrated significantly higher plasma levels of CD‐NP in the CES, and greater endothelial coverage of the stent struts compared with a control group (BMS and polymer‐coated stent) at poststenting, as shown in Figure .…”
Section: Dual‐drug‐eluting Stentsmentioning
confidence: 98%
“…Clinical results have shown that snake venom-derived compounds, such as Dendroaspis natriuretic peptide (DNP), may offer superior therapeutic benefits in chronic HF [14]. This is likely due to greater potency and increased stability as compared to human family members [15,16], while displaying similar benefits in cardiac ischemia through natriuretic receptor-mediated signaling [17,18].…”
Section: Introductionmentioning
confidence: 99%